2001
DOI: 10.1592/phco.21.3.275.34209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adjunctive Treatment with Combined Cytokines in a Neutropenic Mouse Model of Multidrug‐Resistant Enterococcus faecalis Septicemia

Abstract: This study suggests that adjunctive application of combined cytokines may not be more beneficial than only G-CSF in combination with an antibiotic to treat multidrug-resistant enterococcal infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Previous studies in our laboratory and elsewhere have shown that cytokine effect against bacterial infections is influenced by the level of infectious burden [7,9,[23][24][25]. The MLD (LD 100 ) of PSA used in the present study could be overwhelming for the hosts coupled with the virulence characteristics of PSA in acute infection [4].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous studies in our laboratory and elsewhere have shown that cytokine effect against bacterial infections is influenced by the level of infectious burden [7,9,[23][24][25]. The MLD (LD 100 ) of PSA used in the present study could be overwhelming for the hosts coupled with the virulence characteristics of PSA in acute infection [4].…”
Section: Discussionmentioning
confidence: 94%
“…The major findings in this study were that interferon gamma had no benefit on its own and that a combination of IFN-␥ as an adjunct to ceftazidime resulted in no improvement in therapy of PSA pneumonia in both immunocompromised and immunocompetent hosts after onset of infection. A few studies on have shown beneficial effect of IFN-␥ in enhancing antibiotic therapy in animal infection models [7,9,22]. The study by Onyeji et al [9] showed adjunctive efficacy of IFN-␥ when combined with gentamicin and vancomycin in the treatment of GVRE in non-neutropenic (NN) mice but not in neutropenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations